Práticas dos preceptores no Programa de Educação pelo Trabalho para a Saúde: (des)integração ensino, serviço e comunidade - Vêloso, Rafaela Braga Pereira (2017)
The configuration of the care occurs through health care practices based on the principles and guidelines of the Unified Health System (SUS). The federal government started in 2008, the Program of Education through Work for Health (PET-HEALTH), with the sponsorship of learning groups tutorial in strategic areas of SUS. It is relevant to foster discussions about caring, teaching and managing health practices, which requires the qualification of the preceptor. This study aimed to analyze the practices developed by the tutors of the PET-Health and the integration education-service and community in the family health strategy in Feira de Santana, Bahia, Brazil. This is a qualitative study of the type exploratory. The participants were professionals members of the family health team linked to health units that they work as preceptors of the PET - Family Health from 2009 to 2014. The data collection occurred through semi-structured interview, the application of the Technique of Free Association of Words and the analysis of program reports in the period from March to April of 2016, after submission and approval of the project by an Ethics and Research Committee with Human Beings. The method of analysis consists of an approach of the Hermeneutic-Dialectic, which provides a way of the social thinking. The results shows that the approach of health professionals from the family health units of the municipality with the university is favored by the programa. The preceptory is referred to as support and supervision of the activities with users in the service and in the community. The inclusion of students from several undergraduate courses in the health area at USF broadens the range of actions offered in the service and contributes to the process of knowledge production. The actions promoted by the program, stand out from more traditional to fun activities and cultural. The university was pointed as an institution of support to the service. It was emphasized that the clinical practice is privileged rather than the educational activities which shows that activities related to the clinical are central in actions instead of the collective health. In this sense it is imperative to qualify the different social actors involved in the strategies experienced in the program. The important role of the preceptor in strengthening SUS and in the training of health students, makes a permanent education policy necessary for workers.